2019
DOI: 10.1155/2019/4057143
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Goji Berries Does Not Affect Postprandial Energy Expenditure and Substrate Oxidation in Healthy, Overweight Men

Abstract: Background and Aim. Increasing energy expenditure is an effective strategy for the prevention of obesity. In this respect, Lycium barbarum (goji berry) is of interest, as it has been shown to increase postprandial oxygen consumption. Although this suggests that energy expenditure was also increased, energy expenditure and substrate oxidation can only be assessed accurately when both oxygen consumption and carbon dioxide production are measured. We therefore investigated the effects of a single dose of Lycium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…However, a meta-analysis of the effects of L. barbarum supplementation on cardiometabolic risk factors, which included 548 subjects, indicated only a favourable effect on glucose control, and a marginal reduction in total cholesterol and triglyceride levels, without any benefit to body weight and blood pressure [ 97 ]. Moreover, a single dose of 25 g of dried L. barbarum fruits did not influence the postprandial energy expenditure, plasma glucose, serum-free fatty acids, and triglycerides concentrations in healthy, overweight men [ 93 ].…”
Section: Health Benefits and Side Effects Of Goji Berry Consumptionmentioning
confidence: 99%
“…However, a meta-analysis of the effects of L. barbarum supplementation on cardiometabolic risk factors, which included 548 subjects, indicated only a favourable effect on glucose control, and a marginal reduction in total cholesterol and triglyceride levels, without any benefit to body weight and blood pressure [ 97 ]. Moreover, a single dose of 25 g of dried L. barbarum fruits did not influence the postprandial energy expenditure, plasma glucose, serum-free fatty acids, and triglycerides concentrations in healthy, overweight men [ 93 ].…”
Section: Health Benefits and Side Effects Of Goji Berry Consumptionmentioning
confidence: 99%
“…Lycium barbarum L. berry, known as wolfberry or goji berry, is a fruit widely used in Chinese medicine as a bioactive food due to its wide potential health benefits. Various components have been identified, such as carotenoids, fatty acids, fibers, flavonoids, glycerogalactolipids, organic acids, phenolic acids (chlorogenic, caffeic acid, p-coumaric acids, quercetin, and kaempferol), polysaccharides, sugars (fructose, glucose, and sucrose), terpenoids, minerals, and vitamins, which are responsible for the beneficial effects of this berry (Masciet al, 2018;Mocan et al, 2019;Spano et al, 2021;Tian et al, 2019;Zou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, L. barbarum polysaccharides are macromolecular watersoluble glycoconjugates extracted from goji berry with antioxidant, anticancer, antidiabetic, antiaging, neuroprotective, immunomodulatory, and cytoprotective properties (Tian et al, 2019;Zhao, Jing et al, 2023). A ciabatta bread enriched with goji fresh flesh puree showed the ability to protect against lipid peroxidation and inhibitory activities against key enzymes of MetS (α-amylase and α-glucosidase) (Sicari et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the consumption of the algae spirulina (Arthrospira platensis or maxima) or wakame (Undaria pinnatifida) by non-hypercholesterolemic men and women for 17 days did not affect serum lipid or plasma glucose concentrations, and blood pressure [7]. In another study, we examined the acute effects of a single dose of goji berries (Lycium barbarum fruit) on postprandial triacylglycerol and glucose concentrations in healthy, but overweight men [8]. Again, no effects of the intervention on these parameters could be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Sample size calculations were based on the primary outcome parameters, cholesterol-standardized serum campestral concentrations, and energy expenditure for the algae study and goji study respectively[7][8] …”
mentioning
confidence: 99%